In other news negotiating a shifting notion of newsworthiness through amateur web video - Canlas, Daphne-Tatiana T. (Plaridel, 2015)
Access online through this link: https://www.plarideljournal.org/article/in-other-news-negotiating-a-shifting-notion-of-newsworthiness-through-amateur-web-video